Self Efficacy dan Lingkungan Kerja: Booster Utama Employee Engagement - Astrid Ervira R Dewi; Yanto Prasetyo; Diah Sofiah (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2026)
This study aims to determine the relationship between self-efficacy and perception of the work environment with employee emong employees of PD Pasar Surya Surabaya. The research subjects consisted of 51 employees using saturated sampling techniqes. Data were collected using self-efficacy scales, work environement scale, and employee engagement scales. Data analysis techniques used multiple regression analysis. The results showed a significance of 0,000 (p<0,01) with an F value of 12,115, which means that there is a significant simultaneous relationship between self-efficacy, and perception of the work environment with employee engagement. Partially, self-efficacy has significant positive relationship with employee engagement. Partially, perception of the work environment also has a significant positive relationship with employee engagement. Keywords: Self Efficacy, Perception Of The Work Environtment, Employee Engagement, Employee Penelitian ini bertujuan untuk mengetahui hubungan antara self efficacy dan persepsi terhadap lingkungan kerja dengan employee engagement pada karyawan PD Pasar Surya Surabaya. Subjek penelitian berjumlah 51 karyawan dengan menggunakan teknik sampling jenuh. Data dikumpulkan menggunakan skala self efficacy, skala persepsi terhadap lingkungan kerja, dan skala employee engagement. Teknik analisis data menggunakan analisis regresi berganda. Hasil penelitian menunjukkan signifikansi 0,000 (p<0,01) dengan nilai F sebesar 12,115, yang berarti terdapat hubungan simultan yang signifikan antara self efficacy dan persepsi terhadap lingkungan kerja dengan employee engagement. Secara persial, self efficacy memiliki hubungan positif yang signifikan dengan employee engagement. Dan secara persial Persepsi terhadap lingkungan kerja juga memiliki hubungan positif yang signifikan dengan employee engagement. Kata kunci: Self Efficacy, Persepsi Terhadap Lingkungan Kerja, Employee Engagement, Karyawan